Law Enforcement for Culinary Business Actors for Violations in Obligations in Implementing Education and Protocol of Covid-19 Prevention in Jakarta - Wahyu Nugroho (Universitas Negeri Semarang, 2022)
The Special Capital Region of Jakarta (Indonesian: Daerah Khusus Ibukota/DKI Jakarta) has various regulations in enforcing the health protocol law, imposing sanctions on culinary business actors for various violations committed, in terms of not carrying out educational obligations and Covid. -19 prevention protocols. The problems in this research are first, how is law enforcement for culinary business actors who violate the obligation to implement education and Covid-19 prevention protocols in Jakarta? and second, does the imposition of sanctions for culinary business actors have a deterrent effect and can increase awareness in conducting education regarding the Covid-19 prevention protocol? Normative and empirical juridical research methods. Data collection techniques through document/library studies and interviews. A qualitative juridical analysis is based on primary data and secondary data. The results of the first study and conclusions, Law enforcement for culinary business actors are carried out by the Civil Service Police Unit (Indonesian: Satuan Polisi Pamong Praja/Satpol PP) by involving several relevant agencies, as the party overseeing culinary business licensing. Law enforcement is carried out through administrative sanctions ranging from written warnings, and fines, to freezing and revocation of permits. Second, the imposition of various sanctions for culinary business actors can increase awareness in conducting education regarding the Covid-19 prevention protocol, have new habits, and provide a deterrent effect. His advice is that corrective action is needed on policies to handle COVID-19 in the culinary business sector and evaluation of culinary licensing in Jakarta.